1963
DOI: 10.1021/jf60127a010
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils, Determination of Botanical and Geographical Origin of Spearment Oils by Gas Chromatographic and Ultraviolet Analyis

Abstract: If the techniques of Ribéreau-Gayon are used, the authors' observations on the pigments of Vitis labrusca var.Concord more nearly compare with data presented by him for Vitis labrusca. Bearing in mind that the variety of Vitis labrusca used by Ribéreau-Gayon was not specified and may not have been Concord, the authors find the following differences. Fourteen anthocyanin pigments, instead of 11, are found in Concords. Cyanidin 3-monoglucoside is present in much larger amounts than found by Ribéreau-Gayon. Malvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1963
1963
1991
1991

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…Previous work by the authors has shown that the geographical and botanical origin of medicinal plants can be determined with a high degree of accuracy by microanalysis of their essential oils (8,(12)(13)(14)(15)(16). Studies that will present such data for oil of marihuana will be the subject of a forthcoming publication.…”
Section: Composition Of the Essential Oilmentioning
confidence: 99%
“…Previous work by the authors has shown that the geographical and botanical origin of medicinal plants can be determined with a high degree of accuracy by microanalysis of their essential oils (8,(12)(13)(14)(15)(16). Studies that will present such data for oil of marihuana will be the subject of a forthcoming publication.…”
Section: Composition Of the Essential Oilmentioning
confidence: 99%
“…Constituents were characterized by the serial dilution technique (9) and infrared examination of effluents collected following repeated sample injections and rechromatographed under optimal conditions of temperature and carrier gas flow rate (10). Rigorous comparison of retention times and infrared spectra with those of authentic specimens examined under the same experimental conditions was made for coinpound identification.…”
Section: I Gas Chronzatography Of Essential Oil and Isolated Fracmentioning
confidence: 99%
“…3.2.1 Oils Rich in Carvone with More or Less cis-and trans-dihydrocarvone and Their Related Alcohols and Acetates Carvone, dihydrocarvone, and their related compounds carveol, carvyl acetate, dihydrocarveol, and dihydrocarvyl acetate have been found as main components in a number of "spearmint oils" (Smith et al 1963;Lawrence 1978;Maffei et al 1986). The two main types of spearmint oil produced commercially, mainly in the United States, are the Scotch spearmint and the Native spearmint oil (Lawrence 1985).…”
Section: Oils Rich In 2-substituted Compoundsmentioning
confidence: 99%